Atmospheric CO2 Concentration and N Availability Affect the Balance of the Two Photosystems in Mature Leaves of Rice Plants Grown at a Free-Air CO2 Enrichment Site - Ozaki, Hiroshi; Tokida, Takeshi; Nakamura, Hirofumi; Sakai, Hidemitsu; Hasegawa, Toshihiro; Noguchi, Ko (Frontiers in Plant Science, 2020)
Atmospheric CO2 concentration ([CO2]) has been substantially increasing. Responses of leaf photosynthesis to elevated [CO2] have been intensively investigated because leaf photosynthesis is one of the most important determinants of crop yield. The responses of photosynthesis to elevated [CO2] can depend on nitrogen (N) availability. Here, we aimed to investigate the significance of the appropriate balance between two photosystems [photosystem I (PSI) and photosystem II (PSII)] under various [CO2] and N levels, and thus to clarify if responses of photosynthetic electron transport rates (ETRs) of the two photosystems to elevated [CO2] are altered by N availability. Thus, we examined parameters of the two photosystems in mature leaves of rice plants grown under two [CO2] levels (ambient and 200 µmol mol-1 above ambient) and three N fertilization levels at the Tsukuba free-air CO2 enrichment experimental facility in Japan. Responses of ETR of PSII (ETRII) and ETR of PSI (ETRI) to [CO2] levels differed among N levels. When moderate levels of N were applied (MN), ETRI was higher under elevated [CO2], whereas at high levels of N were applied (HN), both ETRII and ETRI were lower under elevated [CO2] compared with ambient [CO2]. Under HN, the decreases in ETRII and ETRI under elevated [CO2] were due to increases in the non-photochemical quenching of PSII [Y(NPQ)] and the donor side limitation of PSI [Y(ND)], respectively. The relationship between the effective quantum yields of PSI [Y(I)] and PSII [Y(II)] changed under elevated [CO2] and low levels of N (LN). Under both conditions, the ratio of Y(I) to Y(II) was higher than under other conditions. The elevated [CO2] and low N changed the balance of the two photosystems. This change may be important because it can induce the cyclic electron flow around PSI, leading to induction of non-photochemical quenching to avoid photoinhibition.